Alternatywność i innowacyjność w edukacji współczesnej – na przykładzie Czech - Zamojska, Eva (Wydawnictwo Naukowe Uniwersytetu im.Adama Mickiewicza w Poznaniu, 2012)
The article in its introduction does present an attempt of facing the dificulties in defining alternativity and innovation in education, taking as the basis opinions of Polish and Czech pedagogists and theoreticians. Second part of the paper is made by a description of examples of alternative and innovative educational activities undertaken in contemporary Czech Republic.
Alternative and Innovative Approach in Modern Education – on the Example of Czech Republic
Keywords: educational alternatives; educational innovations; education in Czech Republic